Islamic Values in Environmental School Culture: Character Formation and Challenges - Ahmad, Victor Imaduddin; Ali, Nur; Zuhriyah, Indah Aminatuz (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to examine how Islamic values are integrated into the environmental school culture within the Adiwiyata program and to analyze the internal challenges in value internalization that affect the formation of students' ecological character. Employing a qualitative multicase study approach, data were collected from two Adiwiyata schools—MAN 1 Lamongan and SMAN 1 Lamongan—through interviews, observations, and document analysis involving 26 purposively selected participants. The findings reveal that core Islamic values such as tauhid, khalifah, amanah, and ihsan are embedded in school culture through a three-layered model of organizational culture (basic assumptions, espoused values, and artifacts). Moreover, the study identifies a seven-stage integrative process of value internalization—from establishing foundational beliefs to engaging with external stakeholders—which facilitates a transformative and sustainable environmental culture in schools. Despite these efforts, challenges persist, particularly in aligning symbolic practices with deeper spiritual consciousness among teachers and students. Theoretically, this study contributes to the development of an Islamic-based educational model for environmental character formation by proposing a contextual and replicable framework that bridges spirituality, institutional culture, and ecological pedagogy. Practically, the model offers strategic guidance for Islamic schools and policymakers to foster value-based environmental programs that extend beyond administrative compliance toward long-term behavioral change.